Análise do processo de órteses, próteses e materiais especiais a partir do método de análise dos modos de falhas e efeitos - Moraes, Clayton dos Santos (Universidade do Vale do Rio dos Sinos, 2014)
The failure modes and effects analysis (FMEA) in heal thcare area is being sought by managers that service segment as a consistent way to work adverse events before they happen or have a direct impact on the patient care. One of these processes work environments is the medical practice with orthosis, prostheses and special materials, that happens invariably within critical areas of health institutions, can be a trigger for patient care risks. The orthosis, prostheses and special materials process is critical since definition materials indicated for the intervention, passing by the administrative processes of budgets and authorizations, care actions by request, receipt, preparation and finishing in the use of these materials. Thus, the entire process should be fully adjusted and suited to attend the specific needs of each user. The aim of this study was to evaluate the potential flaws in the orthosis, prostheses and special materials process through the use of FMEA methodology. In order to achieve this goal it has formed an analysis group for review and redefinition of the flowchart of orthosis, prostheses and special materials and after survey of failure modes at each stage of that process. 16 failures in the steps were observed in all and from those, 19 were raised possible causes for their occurrence, as well as 8 potential effects of failures on the patients care. Following this survey group rated the risk index, depending on the severity, occurrence and detection of failure for each part listed effect and actions capable of implementation in order to reduce healthcare risk represented by failures in the orthosis, prostheses and special materials process were raised. It understands that this study may assist hospitals in implementing actions to reduce risk to patients care imputed by orthosis, prostheses and special materials flaws in the process.
Keywords: Garantia da qualidade dos cuidados de saúde; Administração de materiais no hospital; Avaliação de processos (cuidados de saúde); Análise e desempenho de tarefas; Controle de qualidade; Quality assurance; Health Care; Materials management; Hospital; Process assessment (health care); Task performance and analysis; Quality control; ACCNPQ::Ciências da Saúde::Enfermagem